Implementasi Program Smart Inclusive School (SIS) - Ramadhani, Nabilah Dini; Nawangsari, Ertien Rining (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
SMPN 28 Surabaya is one of the inclusive education providers that provides innovative Smart Inclusive School (SIS) programs. However, the implementation of the SIS program is still constrained by unsupportive infrastructure and inadequate teacher competence so that the implementation of the Smart Inclusive School (SIS) program is not optimal. This study aims to look at the implementation of the Smart Inclusive School (SIS) program at SMP Negeri 28 Surabaya using David C. Korten's program implementation suitability model in which there are 3 elements that is, the programs, implementing organizations, and target groups. In the program element, the implementation of Smart Inclusive School has been well understood and implemented by the school as well as PDBK and parents. the implementing organization element, namely regular teachers and special assistants, has been equipped with training so that there is an understanding in handling PDBK. The target group element, namely PDBK and parents, has benefited from the Smart Inclusive School program, although there are still obstacles in adapting the environment for PDBK.